Exploitation of Host Polyubiquitination Machinery through Molecular Mimicry by Eukaryotic-Like Bacterial F-Box Effectors - Abu Kwaik, Yousef; Price, Christopher T. (Frontiers in Microbiology, 2010)
Microbial pathogens have evolved exquisite mechanisms to interfere and intercept host biological processes, often through molecular mimicry of specific host proteins. Ubiquitination is a highly conserved eukaryotic post-translational modification essential in determining protein fate, and is often hijacked by pathogenic bacteria. The conserved SKP1/CUL1/F-box (SCF) E3 ubiquitin ligase complex plays a key role in ubiquitination of proteins in eukaryotic cells. The F-box protein component of the SCF complex provides specificity to ubiquitination by binding to specific cellular proteins, targeting them to be ubiquitinated by the SCF complex. The bacterial pathogens Legionella pneumophila, Agrobacterium tumefaciens and Ralstonia solanacearum utilize type III or IV translocation systems to inject into the host cell eukaryotic-like F-box effectors that interact with the host SKP1 component of the SCF complex to trigger ubiquitination of specific host cells targets, which is essential to promote proliferation of these pathogen. Our in silico analyses have identified at least 74 genes encoding putative F-box proteins belonging to 22 other bacterial species, including human pathogens, plant pathogens, and amoebal endosymbionts. Therefore, subversion of the host ubiquitination machinery by bacterial F-box proteins may be a widespread strategy amongst pathogenic bacteria. The findings that bacterial F-box proteins harbor Ankyrin repeats as protein-protein interaction domains, which are present in F-box proteins of primitive but not higher eukaryotes, suggest acquisition of many bacterial F-box proteins from primitive eukaryotic hosts rather than the mammalian host.